Factors Related to the Incidence of Diarrhea in Toddlers - Dwi Astuti; Yuliana Rahma Putri (Minsight: Midwifery Insight and Innovation Journal, 2025)
Diarrhea is the second leading cause of death in toddlers, causing 525,000 deaths each year. Based on the number of toddler diarrhea cases in Sukoharjo Regency in 2023, the highest number of cases was in the Kartasura Health Center with 1,863 cases. This study is an observational analytical study with a cross-sectional design. This study involved 1,502 mothers with toddlers as its population. The study used a sample of 91 people with the proportional random sampling method and used the Chi-Square bivariate test. Based on the results of the study, it was concluded that there was a relationship between maternal knowledge and the incidence of diarrhea with a p-value of 0.043 (p-value <0.05), there was no relationship between completeness of immunization and the incidence of diarrhea with a p-value of 0.731 (p-value> 0.05), there was no relationship between feces disposal and the incidence of diarrhea with a p-value of 0.291 (p-value> 0.05) and there was no relationship between waste disposal and the incidence of diarrhea with a p-value of 1,000 (p-value> 0.05). Therefore, educational efforts are needed through counseling activities or socialization held by health workers from health centers or integrated health posts to find out the causes of diarrhea, actions taken if toddlers get diarrhea, and prevention of diarrhea in toddlers. The things that affect the incidence of diarrhea in Kartasura District are because mothers of toddlers do not know the right actions if toddlers get diarrhea, do not know the signs if toddlers get diarrhea, and do not know how diarrhea is transmitted.